The Role of a Changing Market Environment for Credit Default Swap Pricing - Julia S. Leppin; Stefan Reitz (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
This paper investigates the impact of a changing market environment on the pricing of CDS spreads written on debt from EURO STOXX 50 firms. A Panel Smooth Transition Regression reveals that parameter estimates of standard CDS fundamentals are time-varying depending on current values of a set of variables such as the ECB's systemic stress composite index, the Sentix index for current and future economic situation, and the VStoxx. These variables describe the market's transition between different regimes thereby reflecting the impact of substantial swings in agents' risk perception on CDS spreads. Overall, our results confirm the importance of nonlinearities in the pricing of risk derivatives during tranquil and turbulent times.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: G13; G15; C33; 330; CDS spreads; Financial Crisis; Panel Smooth Transition